2021
DOI: 10.1038/s41467-021-21672-9
|View full text |Cite
|
Sign up to set email alerts
|

Current-induced switching of proximity-induced ferromagnetic surface states in a topological insulator

Abstract: Electrical manipulation of magnetization could be an essential function for energy-efficient spintronics technology. A magnetic topological insulator, possessing a magnetically gapped surface state with spin-polarized electrons, not only exhibits exotic topological phases relevant to the quantum anomalous Hall state but also enables the electrical control of its magnetic state at the surface. Here, we demonstrate efficient current-induced switching of the surface ferromagnetism in hetero-bilayers consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 41 publications
(83 reference statements)
1
48
0
2
Order By: Relevance
“…[ 45 ] The polarity of the SOT switching is opposite when reverses the external magnetic field from 1 to −1 kOe. The critical switching current density ≈2.4 × 10 6 A cm −2 is obviously lower than other tungsten/ferromagnet bilayers [ 45–47 ] and is similar to topological insulators/CGT, [ 26 ] most likely ascribed to the formation of interfacial W–Te bonding. Note that the thermal effect generated by the current makes the temperature closer to T C , resulting in the reduced Hall resistance of SOT switching to ≈70% of that in the R H – H curve.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…[ 45 ] The polarity of the SOT switching is opposite when reverses the external magnetic field from 1 to −1 kOe. The critical switching current density ≈2.4 × 10 6 A cm −2 is obviously lower than other tungsten/ferromagnet bilayers [ 45–47 ] and is similar to topological insulators/CGT, [ 26 ] most likely ascribed to the formation of interfacial W–Te bonding. Note that the thermal effect generated by the current makes the temperature closer to T C , resulting in the reduced Hall resistance of SOT switching to ≈70% of that in the R H – H curve.…”
Section: Resultsmentioning
confidence: 92%
“…On account of the semiconductive property, electric field gating is the most commonly utilized to enhance the magnetism of 2D ferromagnetic semiconductors. However, the modulation efficiency of this method is quite limited in a very small scale, especially in CGT with T C around 65 K and weak perpendicular magnetic anisotropy (PMA) due to the Heisenberg behavior, [ 23 ] making the upper limit of the operation temperature in CGT‐based devices only around 40 K. [ 24–26 ] Previous studies only showed the PMA modulation of CGT by ionic liquid gating with the extremely low T C unchanged. [ 14 ] In addition, by stronger electrostatic gating, the T C was raised but with extremely weak magnetic anisotropy (a kink in the magnetization curves) and the destruction of its semiconductive property.…”
Section: Introductionmentioning
confidence: 99%
“…[7,13,17,20] Only two types of thin films have been synthesized via molecular beam epitaxy (MBE) in an ultra-high vacuum condition. [21][22][23] Very recently, a few CVD-based synthesis have been reported for binary 2D metal chalcogenide magnetic crystals such as CrSe and FeTe. [24,25] However, to the best of our knowledge, the conventional CVD-based and Following the first experimental realization of intrinsic ferromagnetism in 2D van der Waals (vdW) crystals, several ternary metal chalcogenides with unprecedented long-range ferromagnetic order have been explored.…”
mentioning
confidence: 99%
“…[23][24][25][26][27] A remarkable progress of manipulating the magnetization has been made towards energy-efficiency scheme using such as alloying HM, [11,28] ferrimagnetic-rearearth transition metal alloy, [29][30] two-dimensional van der Waals materials, [31][32][33] and topological insulators (TIs). [1,27,34] Studies have shown that most TI thin films have limited electrical conductivity in the order of ≈10 5 Ω −1 m −1 , [27,34] which is several times lower than that of HMs and their alloys. Thus, alloying materials will give a notable simple and effective way to improve SOT efficiency.…”
Section: Tuning the High-efficiency Field-free Current-induced Deterministic Switching Via Ultrathin Ptmo Layer With Mo Contentmentioning
confidence: 99%
“…More attention has been paid to the non-volatile spintronic devices, due to their faster data transmission and higher density storage capability. [1][2][3] Compared with a two-terminal spin-transfer torque (STT) magnetic tunnel junction (MTJ), a three-terminal spin-orbit torque (SOT) based MTJ separates the read and the write paths, which results in a lower integration density of the SOT based magnetic random-access memory (SOT-MRAM) than that of the STT-MRAM. [4][5][6] However, in STT-MRAM, energy efficiency and reliability issues remain a fundamental challenge.…”
Section: Introductionmentioning
confidence: 99%